Konflik Timor Leste Lepas dari NKRI 1975-1999 : Telaah Teori Konflik Beberapa Ahli (Jurnal Pendidikan Agama dan Teologi, 2025)
This study aims to analyze the Timor Leste conflict from various conflict theory perspectives. By understanding the motives and dynamics underlying the conflict, it is expected to provide deeper insight into the causes and consequences of the Indonesian invasion and its impact on the Timorese people. This study uses a library method with the intention of collecting and analyzing information from various written sources related to theories of international relations and the dynamics of social conflict, starting with topic identification, literature collection, and ending with analysis and synthesis of information to find patterns and relationships between theories and phenomena studied. The results of the study show that the Timor Leste conflict from the Republic of Indonesia between 1975 and 1999 can be analyzed through various conflict theory perspectives, including Realism, Constructivism, and Marxism Theory. Realism Theory helps explain the Indonesian military invasion as an effort to defend national interests, while Constructivism Theory highlights the role of identity and norms in the struggle for independence of the Timorese people. On the other hand, Marxist Theory reveals that economic injustice and social class differences play an important role in triggering conflict. By understanding these three theories, this research provides deeper insights into the causes and dynamics of conflict, and identifies steps that can be taken to achieve a just and sustainable resolution.